A medium for short-distance lovers that exploits an obstructive function to draw them back to face-to-face communications. Issue 19 (2016) - Iwamoto, Takuya; Nishimoto, Kazushi
Abstract: Currently, in Japan we often see couples in cafes or restaurants who use mobile phones and do not speak to each other. By using mobile phones, we can enjoy communicating, gaming, and web browsing with people in remote places. However, as a result, the couples might become lack of communication and it becomes difficult to make good memories even though they are together. Whereas the related research efforts have attempted to mainly support long-distance couples, there are also such issues to be solved for short-distance couples. Accordingly, we have been studying a medium to encourage communications of the short-distance couples. This medium exploits an obstructive function to move their interests from the mobile phones (online) to the partner (offline) without negative feelings. Firstly, we conducted a field research and designed a communication medium that exploits the couple's obstructive behaviors. Then we conducted user studies of the media with couples in a restaurant. As a result, we confirmed that our idea is useful.